Disipadores de fluido viscoso en el comportamiento estructural de un hotel de ocho niveles - Vargas Valdivia, Dany (2024)
Seismic events cause damage and collapse of buildings, resulting in human, material, and economic losses. To improve seismic performance and reduce damage to buildings, viscous fluid dampers are used. The objective of this study was to determine the influence of viscous fluid dampers on the structural behavior of an eight-story hotel in the city of Cajamarca. For this purpose, a geotechnical study was conducted. The static and dynamic seismic analysis of the structure indicates that the maximum displacements and drifts comply with the E.030 code; however, when performing the time-history analysis, the maximum drifts exceeded the permitted limits (0.007). The incorporation of viscous fluid dampers met the target drift (0.0042) of HAZUS for a functional performance level, reducing the drifts in X and Y directions by up to 55% and 65%, respectively. Additionally, the dampers dissipated 70.56% of the seismic energy, with the structure dissipating 29.44%. It is concluded that the integrated dissipation system significantly influences structural behavior, reducing displacements, drifts, and dissipated energy.